2010
DOI: 10.1016/j.ijrobp.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Is a Potential Mediator of Prostate Cancer Metastasis

Abstract: Purpose We examined whether Survivin expression is associated with an increased risk of metastasis in prostate cancer. Methods and Materials A total of 205 patients with T1 (23%) and T2 (77%) prostate cancer were treated with conventional external beam radiation therapy from 1991 to 1993 at the Massachusetts General Hospital. Of the patients, 62 had adequate and suitable-stained tumor material for Survivin analysis. Median follow-up was 102 months (range, 5–127 months). Distant failure was determined on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…Accordingly, this study demonstrates that tumors with a sufficient RCT-induced downregulation of survivin and lower posttreatment expression levels developed significantly fewer cancer relapse and distant metastases, which constitutes an important clinical endpoint in curatively intended treatment of primary rectal cancer. On the contrary, a failure of survivin downregulation was associated with an increased risk to develop distant metastases, that was in line with recent reports on a correlation between a high survivin expression and distant recurrence in T1/T2 prostate (30) and colon cancer (31). This underlines the potential role of survivin in metastatic pathways-beside its antiapoptotic abilities.…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, this study demonstrates that tumors with a sufficient RCT-induced downregulation of survivin and lower posttreatment expression levels developed significantly fewer cancer relapse and distant metastases, which constitutes an important clinical endpoint in curatively intended treatment of primary rectal cancer. On the contrary, a failure of survivin downregulation was associated with an increased risk to develop distant metastases, that was in line with recent reports on a correlation between a high survivin expression and distant recurrence in T1/T2 prostate (30) and colon cancer (31). This underlines the potential role of survivin in metastatic pathways-beside its antiapoptotic abilities.…”
Section: Discussionsupporting
confidence: 89%
“…Survivin as an apoptotic protein may condition tumor aggressiveness and tumor cell invasiveness, including lymph node involvement and distant metastases (22). It has been shown that survivin may determine, via different signaling pathways, the capacity of prostate and breast cancer cells to metastasize (22,23). Single studies have confirmed this potential of survivin in CRC patients.…”
Section: Survivin (Pg/ml) -------------------------------------------mentioning
confidence: 99%
“…Survivin is a member of the inhibitors of apoptosis protein family and is overexpressed in most common human cancers including breast, prostate, pancreatic, and hematological malignancies (16)(17)(18)(19)(20)(21). It plays a vital role in oncogenesis by being involved in both cell cycle control and resistance to apoptosis (22).…”
Section: Introductionmentioning
confidence: 99%